Observing the use of technology for students' independent work on online learning assignments - Weni, Ricka Yusra; Mulyatiningsih, Endang; Sasvito, Nixigo; Zaid, Zaid (Jurnal Konseling dan Pendidikan, 2024)
This research aims to determine students' responses to online learning, the level of student independence in carrying out online learning assignments, differences in the level of independence of students in Fashion, Culinary, and Tourism study programs, the difficulties faced by students when participating in the online learning process and carrying out learning assignments, and Efforts to find solutions when experiencing difficulties following the online learning process. Conducted at SMK N 4 Yogyakarta, this quantitative descriptive research found that student responses to this research were in the medium category at 71.25% (114 students) with an average score of 18.71. Meanwhile, the level of independence in online assignments is in the high category at 78.13% (125 students), with an average score of 62.00. Not only that, there is a difference in independence in carrying out students' online learning assignments in the Fashion and Catering study program, there is no difference in independence between students in the Food and Tourism study program, and there is no difference in independence between students in the Fashion and Tourism study program. On the other hand, the difficulty in online learning assignments in the medium category was 63.75% (102 students) with an average score of 41.03. Lastly, students' efforts when experiencing difficulties were in the high category at 99.37% (159 students), with an average score of 46.37.